National Libraries – A Dumping Ground or a Source of National Knowledge - Larsen, Steen Bille (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
Within the past year something very unusual has taken place – namely a public debate on the national library task. What actually started this debate was that some scholars were voicing their criticism of the Danish legal deposit act for failing to ensure that sufficient collection of texts from the Internet was being effected and that nothing has been done to preserve these texts for posterity. The discussion was concentrating on how to solve the question of the national library’s main obligations – collection, preservation and accessibility in terms of publications on the Internet. Preservation of digital documents is a new task, but the traditional types of material have not disappeared. Thoughts on how to preserve digital documents will influence opinions on how to handle traditional media and are bound to challenge some of the traditions associated with this. The digitisation issue will set the agenda. Priorities will be necessary in order to focus on the media of the future. The answer to this is a Dual strategy for traditional as well as digital media.